2016
DOI: 10.1159/000446648
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic CAG Repeat Numbers in the Androgen Receptor Gene of Female Pattern Hair Loss in a Han Chinese Population

Abstract: Objective: To investigate the association of CAG repeat numbers in the androgen receptor (AR) gene with female pattern hair loss (FPHL) in a Chinese population. Methods: A total of 200 Han Chinese patients with FPHL (142 Ludwig II and 58 Ludwig III cases) and 200 healthy controls were enrolled in this study. The polymorphism of CAG repeat numbers was analyzed by the fluorescent amplified fragment length polymorphism technique. Results: The CAG biallelic mean length was 23.73 ± 2.04 repeats in Han Chinese FPHL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Two other studies have investigated the association between the major M‐AGA susceptibility locus, the X‐chromosomal locus containing the androgen receptor ( AR ) and ectodysplasin A2 receptor ( EDA2R ) genes, and FPHL. These association studies, carried out in a very small Egyptian sample and the above‐mentioned sample of Chinese Han women with FPHL, were each limited to the investigation of the CAG repeat length variant of the AR gene and no association between this and FPHL was found . Fine mapping studies of this locus in AGA have indicated that the CAG repeat length variant is unlikely to be the causative variant and that other variants at this locus show much stronger association with AGA …”
Section: Heritable Factors—the Present Status Of Fphl Genetic Researchmentioning
confidence: 99%
“…Two other studies have investigated the association between the major M‐AGA susceptibility locus, the X‐chromosomal locus containing the androgen receptor ( AR ) and ectodysplasin A2 receptor ( EDA2R ) genes, and FPHL. These association studies, carried out in a very small Egyptian sample and the above‐mentioned sample of Chinese Han women with FPHL, were each limited to the investigation of the CAG repeat length variant of the AR gene and no association between this and FPHL was found . Fine mapping studies of this locus in AGA have indicated that the CAG repeat length variant is unlikely to be the causative variant and that other variants at this locus show much stronger association with AGA …”
Section: Heritable Factors—the Present Status Of Fphl Genetic Researchmentioning
confidence: 99%
“…Our candidate gene sites did not include AR/EDA2R genes. For the AR/EDA2R locus, domestic research has shown that the CAG repeat number in the AR gene may not be a genetic marker of FPHL [ 21 ]. Our combined results support the theory that the pathogenesis of FPHL is not necessarily consistent with that of MAGA.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 30 candidate genes were selected as follows (Table S2): genes related to androgenetic alopecia (AGA) in males, such as AR/EDA2R [6,14], GRID1 and MC4R [15,16], and PPARG, PPARGC1A, and PPARGC1B [17][18][19][20] were included. In addition, genes involved in the steroid hormone synthesis and metabolic pathways and their receptors were selected: SRD5A1, SRD5A2, ESR1, ESR2, and PGR [21,22] as well as HSD3B1, CYP17A1, and CYP19A1 [7,14,23,24].…”
Section: Candidate Gene Selection and The Analysis Of Allele Frequenc...mentioning
confidence: 99%
“…A total of 30 candidate genes were selected as follows (Table S2): genes related to androgenetic alopecia (AGA) in males, such as AR/EDA2R [6,14], GRID1 and MC4R [15,16], and PPARG, PPARGC1A, and PPARGC1B [17][18][19][20] were included. In addition, genes involved in the steroid hormone synthesis and metabolic pathways and their receptors were selected: SRD5A1, SRD5A2, ESR1, ESR2, and PGR [21,22] as well as HSD3B1, CYP17A1, and CYP19A1 [7,14,23,24]. Genes related to itching and pain, which were identified to be related to eFPHL in this study and the HF cycle modulationrelated genes were also selected: CNR1 and CNR2 [25,26], TRPV1 and TRPV3 [27,28], TACR1 [29], and ABCB1, ABCC1, ABCC4, and ABCG2 [30][31][32].…”
Section: Candidate Gene Selection and The Analysis Of Allele Frequenc...mentioning
confidence: 99%